Development of Android Based Online Nurse Test Preparation - Ambar Relawati; Guntur Maulana Zamroni (JUITA : Jurnal Informatika, 2020)
The Indonesian Nurses Competency Test (UKNI) is a process to determine whether a person is worthy to become a nurse in Indonesia. In 2018 the UKNI test was carried out by 55,573 total participants with a pass percentage of 47.15%. This figure is quite low considering the need for nurses in Indonesia which is still quite high. The unpreparedness of participants in facing tests, either readiness in terms of test material or in terms of mentality is one of the causes of the low pass rate of UKNI. Online Nurse Test (ONT) UKNI is expected to be one of the solutions to answer the above problems. ONT UKNI is a mobile application that has been equipped with learning material, try out, and discussion features aimed to help School of Nursing students in facing UKNI test. The development of the ONT UKNI application uses the modified waterfall model and uses the observation approach and literature review in collecting data and materials which will then be used for the development of the ONT UKNI application. ONT UKNI offers new sets of try out questions and discussion feature that may useful for users. Functional tests has been conducted with 100% results so it can be concluded that the ONT UKNI application is suitable for use.Keywords: Android, Mobile Learning Application, UKNI